Determination of Antimicrobial Effect of Extracts Produced from Some Freshwater Algae Using Different Methods - Özpolat, Emine; Sapmaz, Murat (Durmuş Ali ARSLAN, 2024)
Algae are organisms that can be used in agriculture, cosmetics, medicine, industry and many other areas thanks to the many metabolites they contain. There are thousands of species of algae. Some algae species still remain a mystery. In this study, the antimicrobial activity (against Clostridium perfringens, Enterococcus faecalis, Escherichia coli, E. coli O157:H7, Listeria monocytogenes, Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus agalactiae) of extracts (18 different groups) obtained from three different algal species (Ulothrix zonata, Fontinalis antipyretica and Spirogyra gracilis) by two different methods using water, ethanol, methanol and ether were studied by disc diffusion method. According to the results obtained; each algae species, the method of extraction of the extract and the type of solvent used were found to be effective on the antimicrobial properties. In particular the extracts obtained by using the Soxhlet device (Method B) showed more antimicrobial activity against the selected microorganisms, and in this method, it was observed that the antimicrobial activityt was higher in the extracts in which ether was used as solvent.

Algler, içerdikleri birçok metabolit sayesinde tarım, kozmetik, tıp, endüstri ve daha birçok alanda kullanılabilen organizmalardır. Alglerin binlerce türü bulunmaktadır. Bazı alg türleri ise hala gizemini korumaktadır. Bu çalışmada; üç farklı alg türünden (Ulothrix zonata, Fontinalis antipyretica ve Spirogyra gracilis), iki farklı yöntemle; su, etanol, metanol ve eter kullanılarak elde edilen ekstraktların (18 farklı grup) antimikrobiyal aktiviteleri (Clostridium perfringens, Enterococcus faecalis, Escherichia coli, E. coli O157:H7, Listeria monocytogenes Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus agalactiae'ye karşı) disk difüzyon yöntemi ile incelenmiştir. Elde edilen sonuçlara göre; her bir alg türünün, ekstraktın elde edilme yönteminin ve kullanılan çözücü türünün antimikrobiyal özellikler üzerinde etkili olduğu görülmüştür. Özellikle Soxhlet cihazı kullanılarak elde edilen ekstraktların (Yöntem B) seçilen mikroorganizmalar üzerinde daha fazla antimikrobiyal etki gösterdiği ve bu yöntemde çözücü olarak eterin kullanıldığı ekstraktlarda antimikrobiyal etkinin daha yüksek olduğu belirlenmiştir.
Bazı Tatlı Su Alglerinden Farklı Yöntemler Kullanılarak Üretilen Ekstraktların Antimikrobiyal Etkisinin Belirlenmesi
Keywords: Botany (Other); Bitki Bilimi (Diğer)